OPTIMASI PEMBUATAN PAKAN TERNAK DARI LIMBAH CANGKANG TELUR UNTUK PENINGKATAN PRODUKTIVITAS PELAKU UMKM PETERNAK AYAM POTONG - Fitriadi Fitriadi (Jurnal Optimalisasi, 2017)
Egg shell is one of the livestock waste that becomes a problem for the community and foodstuff processing industry made from egg raw. With the massive amount of community consumption, of course, the amount of waste of eggshells will also accumulate and is usually thrown away. So waste eggshell is considered as waste that will be thrown away. Egg shell can be given as animal feed ingredients because it is notdangerous and in egg shells there are still many substances, as well as minerals that are needed by the body of poultry. This study aims to increase the production of chicken breeders through the best alternative feed selection. Making poultry chicken feed through the utilization of eggshell waste with various alternative raw material selection. Determination of the best type of egg shell waste based on nutritional value and quantity of livestock chicken production. This study is expected to reduce environmental pollution from eggshell waste and is expected to contribute relevant to increasing productivity of SMEs broiler farmers.Keywords: Egg Shell, animal feed, broiler farmers